1985
DOI: 10.1139/f85-101
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Learning Ability of Selected Fishes

Abstract: Fourteen species of freshwater fish were trained to execute a simple conditioned response in a shuttle box – to move in response to light to avoid an electrical shock. There was no relation between learning ability and phylogenetic position. Better learners included striped bass (Morone saxatilis), bigmouth buffalo (Ictiohus cyprinellus), common carp (Cyprinus carpio), and channel catfish (Ictalurus punctatus). Bluegill (Lepomis macrochirus) and northern pike (Esoxlucius) were poor learners. Yellow perch (Perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 13 publications
1
29
0
3
Order By: Relevance
“…The observed variation in learned avoidance of B. marinus by native fishes may be due to several factors. There may be inter-and intraspecific variation in the learning ability of fishes (Coble et al, 1985). Thus, some sooty grunter may be better learners than others, while barramundi may, in general, be better learners than sooty grunter.…”
Section: Discussionmentioning
confidence: 99%
“…The observed variation in learned avoidance of B. marinus by native fishes may be due to several factors. There may be inter-and intraspecific variation in the learning ability of fishes (Coble et al, 1985). Thus, some sooty grunter may be better learners than others, while barramundi may, in general, be better learners than sooty grunter.…”
Section: Discussionmentioning
confidence: 99%
“…His experiments (20 individuals with four replications each) revealed that 48 mm L T juveniles were better at learning than 35 mm L T juveniles. Coble et al (1985) reported that older channel catfish Ictalurus punctatus Rafinesque at 250-300 mm body length learned avoidance of electric shock better than did juveniles at 100-120 mm, but there was no difference between juvenile (145 mm) and older (250-320 mm) largemouth bass Micropterus salmoides L. Tsukamoto et al (1995) (five individuals for each size), using reward conditioning. Although their experiment lacked true replication, their results suggest that 100 mm fish learn in the shortest period (six days) and 210 mm require the longest time (33 days).…”
Section: Discussionmentioning
confidence: 99%
“…There is, in fact, an exhaustive list of behavioural variables routinely employed to investigate subjective mental states in animals that has likewise been successfully demonstrated in fish. A variety of fish species have shown avoidance learning (Coble et al 1985), long-term memory (Aronson 1971), conditioned suppression (Geller 1964;Yue et al 2008), social learning (Brown and Laland 2003), operant responding (Anthouard 1987), nociceptive behaviour ), demonstration of complex or flexible behaviour (Topál and Csányi 1999), problem-solving ability (Mizukami et al 1999), demonstrated preferences (e.g. taste aversion) (Little 1977) and capacity to use 'trade-offs' according to 'consumer demand' theory (Dunlop et al 2006).…”
Section: Pain: a Conscious Statementioning
confidence: 99%